Improving Community Values through Digital Marketing Knowledge for UMKM "Sari Markisa Manis" RT 01/RW 08, Mampang Village, Pancoran Mas District, Depok City - Sri Nawangsari; Dyah Mieta Setyawati; Ditiya Himawati; Ade Rachmawati Nurfitri; Wardoyo (Indonesian Journal of Advanced Social Works, 2023)
Business man need increased knowledge and skills in marketing functions that can expand the market for passion fruit juice drink products from harvested "Marquisa Manis Mampang" UMKM actors in Mampang Village, Pancoran Mas District, Depok City. The method used in this activity is to use assistance, counseling and training to business actors "Marquisa Manis Mampang". Improving community values through digital marketing knowledge in marketing management functions is very important in expanding product marketing and maximizing the use of available business actor resources with the assistance of information and communication technology. This Community Service Activity (Abdimas) has inspired the birth of the process of implementing marketing management function activities by Partners, through social media in the form of Instagram and Whatsapp and the use of websites, namely YouTube with the help of using TIK devices, namely mobile phones for business actors "Markisa Manis Mampang" . The scope of product marketing as a result of Abdimas' activities has made the market for "Marquisa Manis Mampang" beverage products have expanded outside the city of Depok, such as Semarang, Medan and Batam. This market expansion has led to an increase in Partners' production capacity and has an impact on increasing the income of the families of business actors.